Fenologia e trocas gasosas da videira cv. Sweet Sunshine em clima semiárido - Souza, Essione Ribeiro; Amaro, Amanda Cristina Esteves [UNESP]; De Sousa Santos, Laíse; Ono, Elizabeth Orika [UNESP]; Rodrigues, João Domingos [UNESP] (Lepidus Tecnologia, 2016)
Several physiological and environmental factors can Influence the development and growth of vines cultivated in irrigated areas of the Brazilian semi-arid region. Therefore, it is necessary to characterize the phenology of 'Sweet Sunshine' grapevine under Sub-medium São Francisco Valley, Brazil conditions in order to set up the managements employed for the crop. To characterize the phenology 12 plants were selected, distributed in four repetitions, from the first growing season, both in the 2nd half of 2012 as in the 1st half of 2013. The observations of plant development phases were initiated immediately after pruning, ending at the harvest. Gas exchange measures as net CO2 assimilation rate, stomatal conductance, transpiration rate, intercellular CO2 concentrations, water use efficiency, apparent carboxylation efficiency (Rubisco) and the photosynthetic photon flux density were performed at inforescence, early flowering, growth and softening of berries phases. The productive characterization was performed weekly, determining the clusters fresh weight length; fresh weight, diameter, length and volume of the berries; soluble solids content and titratable acidity; fresh and dry weight, basal, median and apical diameter of the stems. It was found that physiological parameters induced changes in the characteristics of the plants for the two evaluated periods, since the behavior of the curve for gas exchange measurements were distinct, exhibiting productive and commercial potential.
Phenology and gas exchanges of grapevines cv. Sweet Sunshine grown in semiarid climate
Keywords: Gas exchange; Productive characterization; Semiarid; Vitis vinifera L.